Common Law in an Uncommon Courtroom, Eva N. S. Ng (2018) - Ng, Kwai Hang (International Journal of Speech, Language and the Law, 2019)
Common Law in an Uncommon CourtroomEva N. S. Ng (2018)John Benjamins pp 373